2022
DOI: 10.17221/221/2021-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Foaming properties, microstructure, and mathematical model of foam mat drying of pasta sauce based on tomato

Abstract: In the present study, the foam mat drying technique was used to dry pasta sauce based on tomato to become powder. The effect of different egg white concentrations (3, 6, and 9%) and whipping time (2 min and 5 min) on the foam properties of pasta sauce, including foam density, foam expansion, foam viscosity, water activity, morphological and drying behaviour, were investigated. The foamed sauce was dried in a batch-type thin-layer dryer at constant conditions (temperature of 60 °C). Six thin-layer drying models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The correlation coefficient (R 2 ) with equation 7 and the root mean square error (RMSE) with equation 8 were determined to assess the fit between the model and the experimental data [22]. The highest R 2 and the lowest RMSE is what must be met for the model to be optimal [23].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficient (R 2 ) with equation 7 and the root mean square error (RMSE) with equation 8 were determined to assess the fit between the model and the experimental data [22]. The highest R 2 and the lowest RMSE is what must be met for the model to be optimal [23].…”
Section: Discussionmentioning
confidence: 99%
“…The desirability function was applied to select the optimum conditions for pasta sauce foaming. Afifah et al (2022) reported that a decrease and an increase in density and foam expansion contributed to the effective diffusivity during foam drying. This accelerated drying process maintains product quality by limiting its exposure to hot air.…”
Section: Process Optimizationmentioning
confidence: 99%
“…Sifat et al (2021) reported the significant influence of egg white concentration and whipping time on the foam characteristics of plum powder produced through foam-mat drying. Adjusting these parameters led to the production of tomato sauce with distinct foam properties such as low density, viscosity, and high expansion (Afifah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%